PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU SMPN SE-KECAMATAN KOTA MANNA KABUPATEN BENGKULU SELATAN - Neti Herawati; Rambat Nur Sasongko; Puspa Djuwita (UNIVERSITAS BENGKULU, 2017)
The Objektive of this resears is to know the influence of headmasters leadership and organization culture foward teacher is performance at Junior High School in Subdistrik of manna City.The method of this research was qualitative to prone hyphothesis with statistical analiysis. The subjects of this study were teacher of Junior High School in Subdistrict of Manna City. The data ware taken by distributing questionnaire. Then data analysis used quantitative. The result of this study showed that (1) there was a significant corelation between headmaster’s leadership and teacher’s perfomance (2) there was a significant correlation between organization culture and teacher’s perfomance and (3) there was a significant correlation simultaneously between headmaster’s leadership and organization culture to teacher performance.